Fermented foods as alternative functional foods during post-pandemic in Asia - Wan-Mohtar, Wan Abd Al Qadr Imad; Ilham, Zul; Jamaludin, Adi Ainurzaman; David, Wahyudi; Mohd Zaini, Nurul Aqilah (Frontiers in Food Science and Technology, 2022)
According to research on the COVID-19 pandemic, consumption of a variety of foods, drinks, nutritional supplements, and other substances that could assist the immune system’s defense against the disease is advised. Among these, fermented foods, an age-old method of food preservation, especially in Asia offer better advantages. Fermented foods provide diversity in food products, having unique flavors and aromas as well as acting as functional foods. In other words, fermentation may lessen the effects of COVID-19 by boosting the antioxidant activity of foods and increase immunity by improving digestion, especially in Asia. The purpose of this review was to evaluate the therapeutic responses of fermented foods and the relationship of respective bioactivities toward disease prevention during the COVID-19 pandemic. It has been suggested that traditional fermented foods in Asian countries could increase immunity and act as a first line of defense against the potential COVID-19 infection.